Dairy waste - feed for fish? - Eliasson, Thomas (2015)
Global meat production has increased dramatically in the last 50 years and along with this growth, aquaculture has made a rapid development, now comprising 14.3 % of all meat produced. The growing demand and desire for animal protein will become a real challenge in the future, seafood derived from aquaculture may be a partial solution, showing positive effects on both undernourishment and obesity in humans. But as with other types of animal production, the most demanding challenge is feed supply, there is always the risk of feed ingredients competing with foods for human consumption. In 2008, from major groups of fish and crustaceans cultured, 64.4 % of the production was dependent on external feeds, of which ingredients based on fish and other water-living animals comprised 15.4 %. Further investigations showed that there are major differences in feed consumption (both type of feed and amount) between species due to a wide diversity within their digestive systems and nutrient requirements. Single cell protein (SCP) is a feed source with major potential for aquaculture, supported by the fact that fish and crustaceans possesses the ability to degrade nucleic acids (purines) more efficiently than other animals. A short review based on 10 earlier studies where fish meal was substituted by yeast SCP showed mixed positive and negative results on growth; more research is needed. A goal of this study was to produce SCP from dairy wastewater by fermentation with the yeast Kluyveromyces lactis, and in the process also improve the wastewater for biogas production. The results showed that there may be a beneficial effect for biogas production, whereas the SCP production was less promising. The biomass increased by 57.84 % (after 30 hours of fermentation), which is positive. Though, further analysis of the pelleted biomass indicated a decreasing concentration of crude protein per kg dry matter.